1990
DOI: 10.1007/bf00297229
|View full text |Cite
|
Sign up to set email alerts
|

Organization of a phyllobranchiate gill from the green shore crab Carcinus maenas (Crustacea, Decapoda)

Abstract: The phyllobranchiate gills of the green shore crab Carcinus maenas have been examined histologically and ultrastructurally. Each gill lamella is bounded by a chitinous cuticle. The apical surface of the branchial epithelium contacts this cuticle, and a basal lamina segregates the epithelium from an intralamellar hemocoel. In animals acclimated to normal sea water, five epithelial cell types can be identified in the lamellae of the posterior gills: chief cells, striated cells, pillar cells, nephrocytes, and gly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
33
0
7

Year Published

1992
1992
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(48 citation statements)
references
References 29 publications
8
33
0
7
Order By: Relevance
“…The respective part of mercury taken up in the gill tissue and that adsorbed on the biofilm could not be quantified in the present study. As the algal coat is well known to be variable according to the stage of the molt cycle (Goodman & Cavey 1990), this could concomitantly result in large differences in mercury uptake and storage.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The respective part of mercury taken up in the gill tissue and that adsorbed on the biofilm could not be quantified in the present study. As the algal coat is well known to be variable according to the stage of the molt cycle (Goodman & Cavey 1990), this could concomitantly result in large differences in mercury uptake and storage.…”
Section: Discussionmentioning
confidence: 99%
“…Pillar cells also hold up a central sheet of conjunctive tissue called the intralamellar septum. There are 5 main cell types in the gill lamellae (Goodman & Cavey 1990, Taylor & Taylor 1992: epithelial cells that are either thin (chief cells) or thick and mitochondria-rich (striated cells), pillar cells, nephrocytes and glycocytes in the lamellar septum and gill shaft. Fig.…”
Section: Autometallographic Localization Of Mercury In Gill Tissuementioning
confidence: 99%
See 1 more Smart Citation
“…The comparison with other species demonstrated that the gill epithelium is only slightly differentiated in P. japonicus. In other species such as Gecarcinus lateralis (COPELAND & FITZJARREL, 1968), Carcinus maenas (GOODMAN & CAVEY, 1988, 1990COMPERE et al, 1989) and Procambarus clarkia (BURGGREN et al, 1974), two types of epithelia coexisted in the gill, a thin one supposedly implicated in gas exchange, and a differentiated epithelium involved in hydromineral exchanges. In adult P. japonicus, only one type of epithelium with apical microvilli but without basal enfoldings could be observed (BOUARICHA et al, 1994).…”
Section: Introductionmentioning
confidence: 99%
“…In crustacean gills, the basolateral membranes are closely associated with high numbers of prolonged mitochondria. Mitochondrial densities and lengths become reduced in the regions beneath the apical membrane layers; while apical membranes themselves are seemingly not associated with mitochondria (Copeland & Fitzjarrel, 1968;Goodman & Cavey, 1990).…”
Section: Introductionmentioning
confidence: 99%